Fertility control of rodent pests - Jacob, Jens; Singleton, Grant R.; Hinds, Lyn A. (Commonwealth Scientific and Industrial Research Organisation, 2008)
Ricefield rats (Rattus argentiventer) in south-east Asian rice fields and house mice (Mus domesticus) in Australian grain fields are major pest species. They cause damage before and after harvest and carry zoonotic diseases. For both species, management techniques have been pursued using the approach of immunocontraceptive vaccination. We review results from a series of enclosure and field studies conducted with these species to assess the effects of fertility control in small rodents. In the experiments, fertility control was simulated by tubal ligation, ovariectomy or progesterone treatment. A once-off sterilisation of 50–75% of enclosed founder females considerably reduced reproductive output of ricefield rat populations until the end of the reproductive period. In house mice, similar success was achieved when a sterility level of 67% of female founders and offspring was maintained. Repeated antifertility treatments are required because of the much longer breeding period of house mice versus ricefield rats. Comparing the results of enclosure trials with the outcome of simulation models suggests that partial compensation of treatment effects can occur through enhanced reproduction of the remaining fertile females and improved survival of juveniles. However, such compensatory effects as well as behavioural consequences of sterility in field populations are not likely to prevent the management effect at the population level. The challenge for effective fertility control of small rodents in the field is the wide-scale delivery of an antifertility treatment to founders at the beginning of the breeding season and to fertile immigrants that are recruited into the population, which otherwise contribute to the reproductive output at the population level. Future research efforts should focus on species-specific techniques and on agents that can be effectively delivered via bait.